Application Of Structural Equation Modeling to Identify The Influence Of Divergent Thinking, Self-Efficacy, Critical Thinking, And Self-Regulated Learning On The Learning Outcomes Of Cadets At Aviation Polytechni Surabaya - Yuyun Suprapto; Bambang Bagus Hariyanto; Nyaris Pambudiyatno; Ade Irfansyah; Moch. Rifai (Universitas Negeri Malang, 2025)
Society 5.0 is unavoidable because it is a development of information technology marked by the transformation from analog to digital technology. Society 5.0 is more human centered based on technology. Therefore, this study is considered necessary to examine the characteristics of Human Resources (HR) in society 5.0. HR here refers to cadets who are students of the Surabaya Aviation Polytechnic and will eventually face the world of work. Cadets are human resources who can face challenges in it and are competent in all fields because society 5.0 was born to facilitate quality human life, which is also lived by quality human resources. Using a quantitative approach with Structural Equation Modeling (SEM) analysis, this study involved 216 cadets selected by purposive sampling. This research investigates the influence of Divergent Thinking, Self Efficacy, Critical Thinking, and Self-Regulated Learning on the Learning Outcomes of cadets at Surabaya Aviation Polytechnic by employing the Structural Equation Modeling - Partial Least Square (SEM-PLS) approach. The framework of this study comprises independent variables- namely Divergent Thinking (X1), Self Efficacy (X2), Critical Thinking (X3), and Self-Regulated Learning (X4) and a single dependent variable, Learning Outcomes. Emphasizing the role of cognitive and metacognitive competencies, this study highlights their significance in shaping vocational education strategies aimed at equipping graduates for the multifaceted challenges of Society 5.0, particularly within the highly dynamic aviation industry. The findings contribute meaningful perspectives for enhancing curriculum design and instructional practices to strengthen cadets’ competencies and elevate overall academic achievement.